2022
DOI: 10.3390/biomedicines10061420
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Functionality of Neonatal Porcine Islet-like Cell Clusters Bioprinted in Alginate-Based Bioinks

Abstract: The transplantation of pancreatic islets can prevent severe long-term complications in diabetes mellitus type 1 patients. With respect to a shortage of donor organs, the transplantation of xenogeneic islets is highly attractive. To avoid rejection, islets can be encapsulated in immuno-protective hydrogel-macrocapsules, whereby 3D bioprinted structures with macropores allow for a high surface-to-volume ratio and reduced diffusion distances. In the present study, we applied 3D bioprinting to encapsulate the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…It is crucial to consider these parameters to optimize cell viability in the printing process [ 129 ]. Alginate alone and in combination with various polymers has been extensively utilized as a bioink for cell transplantation [ 125 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. For example, while gelatin methacryloyl (GelMA) upon light exposure forms chemically stable hydrogels for cell encapsulation, it was observed that creating uniform and stacked cell-laden fibers using low-concentration GelMA hydrogels can pose challenges for regular printing processes in certain cases [ 141 ].…”
Section: Cell Encapsulation Techniquesmentioning
confidence: 99%
“…It is crucial to consider these parameters to optimize cell viability in the printing process [ 129 ]. Alginate alone and in combination with various polymers has been extensively utilized as a bioink for cell transplantation [ 125 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. For example, while gelatin methacryloyl (GelMA) upon light exposure forms chemically stable hydrogels for cell encapsulation, it was observed that creating uniform and stacked cell-laden fibers using low-concentration GelMA hydrogels can pose challenges for regular printing processes in certain cases [ 141 ].…”
Section: Cell Encapsulation Techniquesmentioning
confidence: 99%
“…2 ) [ 18 , 71 , 72 ]. Most importantly, it can provide a proper niche for cells as it resembles another polysaccharide in the native ECM – hyaluronic acid – moreover it can simultaneously act as a suitable immuno-protective barrier for their delivery into the body [ [73] , [74] , [75] ]. It can simulate a niche that offers specific external conditions for cell attachment, proliferation, differentiation, as well as migration, thereby promoting tissue regeneration.…”
Section: Alginate's Propertiesmentioning
confidence: 99%
“…[11] During alginate crosslinking and the subsequent cultivation, the methylcellulose is partially released, forming a crosslinked construct of mainly alginate.. [11,12] This versatile ink has been successfully applied for bioprinting of various mammalian cell types such as pancreatic islets of Langerhans and chondrocytes, but also for bioprinting of microalgae. [13][14][15][16][17][18][19] Based on the promising results in these ground-based studies, Alg-MC was the first bioink to be selected by the company OHB for use in space. As part of the ISS mission Cosmic Kiss of the German ESA astronaut Matthias Maurer, it was used as one of two for the mission selected bioinks to generate constructs with the aid of a hand-held printer, which in combination with dermal fibroblasts should later provide rapid assistance in the wound closure of large-area skin injuries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] During alginate crosslinking and the subsequent cultivation, the methylcellulose is partially released, forming a crosslinked construct of mainly alginate.. [ 11,12 ] This versatile ink has been successfully applied for bioprinting of various mammalian cell types such as pancreatic islets of Langerhans and chondrocytes, but also for bioprinting of microalgae. [ 13–19 ]…”
Section: Introductionmentioning
confidence: 99%